HUBUNGAN BEBAN KERJA PERAWAT DENGAN RESPON TIME PADA PENANGANAN PASIEN DI INSTALASI GAWAT DARURAT RUMAH SAKIT IBNU SINA MAKASSAR - said, sahrul; Mappanganro, Andi (Journal of Islamic Nursing, 2018)
The dangerous patient Service emergency is service that need it helping soon that is fast, correct and accurate to to prevent death and defectness, or the dangerous patient service emergency to hold role that very important Time saving is life saving that time is soul , factor that influence patient's service its between is load work nurse and time's response . Research this knower have go to exist its not connection of load work nurse with time's response . This Research is done in IGD Hospital Ibnu Sina Makassar. This Research is research type survai analitik with approach Crosssectional. This Research is done with direct Observation by examiner. Research Sample to add 21 responden who fulfill criteria inklusi with to use it sampling's total as sample with drawal technique. The data Analysis that to be used is bivariat's analysis. Analysiical Result load bivariat connection work nurse with time's response to patient's handling in Emergency Dangerous Installation Hospital Ibnu Sina Makassar with to use it test Fisher's Exact be obtained value ρ = 0,673, where value ρ bigger from α = 0,05 so H0 be accepted and Ha be refused. Research result To be based, show that there is no the significant connection between load work nurse with response time to patient's handling in Emergency Dangerous Installation Hospital Ibnu Sina Makassar 2016. To be suggested to installation, so that always to arrest it and level it time's response that according to with standard that to be decided also service quality hospital still to be leveled.